Synthesis of alkylene-bridged diphenyl-oligoynes - Klinger, Christian; Vostrowsky, Otto; Hirsch, Andreas (European Journal of Organic Chemistry, 2006)
A general synthesis route for the preparation of oligoynes stabilized by alkylene bridges is reported. The corresponding macrocycles contain oligoynes with up to eight conjugated triple bonds. The stabilization of the conjugated sp-oligoyne rods was achieved by bulky terminal phenylic endcaps spanning the alkylene chain to isolate the individual acetylenic rods and to avoid polymerization. Alkylene chains with up to 40 methylene groups were employed. The two terminal acetylene functions were introduced prior to the oligoyne elongation by twofold introduction of additional C-acetylene or C-butadiyne building blocks. The final step was the intramolecular acetylene coupling upon which very large macrocycles with up to 62 ring members containing segregated sp-, sp- and sp-segments were formed. © Wiley-VCH Verlag GmbH & Co. KGaA, 2006.